An in vitro comparative antibacterial study of different concentrations of green tea extracts and 2% chlorhexidine on Enterococcus faecalis - Leena P Martina; Ambrose Vedamanickam Rajesh Ebenezar; Mohamed Fayas Ghani; Ashwin Narayanan; Meenakshi Sundaram; Ajit George Mohan (Wolters Kluwer Medknow Publications, 2013)
Aim : The purpose of this study was to comparatively evaluate the antibacterial property of various concentrations of green tea extracts and 2% chlorhexidine (CHX) against Enterococcus faecalis 0(E. faecalis) in vitro. Materials and Methods: The activity of green tea extract and CHX on E. faecalis was measured on agar plates using the agar diffusion method. In addition, the tube dilution method was used to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration of green tea extract against E. faecalis. Results: The MIC of green tea extract was found to be 3.5%. The zone of inhibition was found to be concentration dependent. The 2.5% concentration of green tea extract showed 20 mm zone of inhibition, while the 3% concentration demonstrated a 30 mm zone of inhibition. Two percent CHX showed 30 mm zone of inhibition. Conclusion: Three percent concentration of green tea extract showed an antibacterial activity equivalent to 2% CHX against E. faecalis.